Heat Exchanger Design for WO3 Synthesis using Hydrothermal Method - Lianawati, Maya; Nandiyanto, Asep Bayu Dani; Kurniawan, Teguh; Ragadhita, Risti (CHEMTAG Journal of Chemical Engineering, 2023)
This study aims to analyze a heat exchanger (HE) design in the synthesisof WO3 using hydrothermal method. The data were calculated using Microsoft Excel application using several parameters and assumption. The result found that shell and tube designed heat exchanger have 80.04% effectiveness with initial heat transfer (Q) 383197 and some specifications included. However this result further calculation for fouling factor and appropriate value for TEMA standards.